Employee Personality and Enterprise Management - Huiying Liu; Ning, Jipu (International Journal of Management and Education in Human Development, 2022)
With the continuous improvement of modern enterprise management, the management of the individuality of employees has gradually occupied a core position. While employees realize their self-worth, they also maximize the benefits of the company. This is the pursuit of long-term corporate managers and sustainable development. Any employee in the company has his own personality, but among the personalities displayed by the employees, some individual employees are conducive to teamwork, while some individual employees destroy the corporate team strength. For example, some employees have their own personalities. Own personality and ignore the existence of other employees or not adopt the opinions of other members of the team, etc., this is a kind of "damage" to the overall combat effectiveness of the team. Therefore, any employee has an "angel" side and also a "devil" side. This is especially true for individual employees. Therefore, the essence of managing individual employees is to allow individual employees to "hide" the "devil" side and show The "angel" side in turn facilitates teamwork and improves team performance. Because employees have different personalities, they have different outlooks on life, world outlook, and values. They have different views on what happens in work and life. When there are obvious differences, especially in the way of benefit distribution, it is easy to cause conflicts. Therefore, managers must carefully understand the individual characteristics of employees and strive to achieve the complement of employees, so as to reduce internal consumption and enhance organizational cohesion. Team spirit is an indispensable spiritual pillar in organizational management. On this basis, managers must respect and guide employees to play their own personal characteristics, so that their personality can be fully displayed. Eventually, each employee and department can achieve coordinated development, which is ultimately conducive to the realization of organizational value.